Method for stirring two-component type sealing material composition
Through specific stirring methods and equipment, the problem of insufficient mixing of two-component sealants is solved, and the uniformity and performance of the sealant are improved.
Patent Information
- Application Number
- JP2023156600
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2043-09-22
AI Technical Summary
In the prior art, when using two-component sealants, it is difficult to achieve sufficient mixing, resulting in uneven surface of the sealant and increasing over time, affecting appearance and performance.
Specific stirring methods and equipment are adopted, including the use of a bottom cylindrical stirring container, a central rotating shaft, a bottom wrench and a side wrench, to ensure that the sealant is fully mixed by adjusting the stirring parameters such as the average liquid height, wrench height, side wrench length and stirring temperature.
Full mixing of two-component sealants is achieved to prevent surface unevenness and appearance deterioration, and the physical properties of the sealants are improved.
Smart Images

Figure 2025047847000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for mixing a two-component sealant composition. [Background technology]
[0002] Sealants are widely used in buildings and the like to fill joints and gaps between various members to ensure watertightness, airtightness, etc. For example, Patent Document 1 discloses a two-component sealant composition containing a polymer having a hydrolyzable silyl group, a resin hollow body, calcium carbonate, and silicon dioxide in a predetermined amount. The two-component sealant composition described in Patent Document 1 was developed with the aim of making the unevenness of the sealant surface less noticeable, providing excellent design, and also providing excellent workability and durability.
[0003] When the sealant composition is of two-component type, it is common to mix the two-component sealant composition uniformly and harden it at the construction site using a mixer with a stirring blade. For example, Patent Document 2 discloses a method of mixing a urethane-based two-component sealant using a mixer equipped with a paddle having a pair of stirring blades with different distances to the rotation axis or a pair of stirring blades with different upper and lower lengths.
[0004] On the other hand, it has been found that a sealant composition containing resin hollow bodies may cause dents on the surface of the sealant obtained after curing, resulting in poor appearance. As a method for preventing the occurrence of such dents, for example, Patent Document 3 discloses a construction sealant containing a modified silicone resin, a plasticizer, a curing accelerator, an inorganic filler, and an organic filler, in which a hollow filler made of a polyacrylonitrile resin is used as the organic filler, the content of the hollow filler is 0.1 to 0.6 mass%, and the true specific gravity of the hollow filler is 0.1 to 0.5. It is considered that Patent Document 3 attempts to suppress the occurrence of dents on the surface of the sealant by limiting the resin composition, content, true specific gravity, etc. of the hollow filler. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-127357 [Patent Document 2] JP 2006-204980 A [Patent Document 3] JP 2014-15530 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present inventor prepared a sealant by stirring the two-component sealant composition described in Patent Document 1 by the method described in Patent Document 2, and confirmed that the obtained sealant may have no problem immediately after mixing, but may have increased surface unevenness and deteriorated appearance over time. In addition, it was confirmed that if the height of the stirring blade is lowered to prevent the occurrence of unevenness, mixing becomes insufficient. On the other hand, the method of limiting the resin composition, blending amount, and true specific gravity of the resin hollow body as described in Patent Document 3 may not be able to impart the desired physical properties to the sealant. Therefore, the present invention aims to provide a stirring method that can thoroughly mix a two-component sealant composition containing a resin hollow body and prevent surface unevenness and deterioration of appearance that may increase over time after the composition is cured. [Means for solving the problem]
[0007] In order to achieve the above object, in one embodiment, the present invention has the following configuration. [1] A method for stirring a two-component sealant composition comprising a base containing a resin hollow body and a curing agent, the method comprising the steps of: The two-component sealant composition is mixed using a stirring device having a bottomed cylindrical mixing container into which the two-component sealant composition is supplied, a rotating shaft rotatably provided in the center of the mixing container by a driving device, a bottom paddle provided at the lower end of the rotating shaft, and a pair of side paddles extending from both ends of the bottom paddle along the inner wall of the mixing container to the upper end, The average base liquid level height LL (mm) when the base is supplied to the mixing vessel, the height H (mm) of the pair of side paddles, the average radius X (mm) of the bottom paddle, the initial viscosity A (Pa s) of the base at the temperature during mixing, the initial viscosity B (Pa s) of the base at 5° C., and the cube root C of the value obtained by dividing B by A, Y=(LL-H)×C, are expressed by the following formula 1: Equation 1 0.2X≦Y≦0.4X A stirring method characterized in that the above-mentioned is satisfied. [2] The mixing method according to [1], wherein the resin hollow bodies are contained in an amount of 0.8 to 10 parts by mass relative to 100 parts by mass of the base. [3] The volume S(L) of the two-component sealant composition present at a height from the lowest position to the highest position where the pair of side paddles pass relative to the total volume R(L) of the two-component sealant composition before stirring is expressed by the following formula 2: Formula 2 13≦Z=100×(RS) / R≦23 The stirring method according to [1] or [2], which satisfies the above. [4] A method for producing a sealant, comprising the steps of: stirring a two-component sealant composition comprising a base containing hollow resin bodies and a curing agent by the stirring method described in any one of [1] to [3]; and applying the stirred two-component sealant composition to an object. Effect of the Invention
[0008] The stirring method of the present invention can thoroughly mix a two-component sealant composition comprising a base containing hollow resin bodies and a curing agent, and can prevent surface irregularities and deterioration in appearance that may occur over time after such a composition is cured. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of a stirring device used in a stirring method according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a paddle of a stirring device used in a method according to one embodiment of the present invention. [Diagram 3] 1 is a photograph of a stirring device used in the examples. [Figure 4] Photographs of the surfaces of sealants obtained by stirring and casting the two-component sealant compositions prepared in each of the Examples and Comparative Examples in an atmosphere at 5° C. are shown. [Diagram 5] 1 is a photograph of the surface of a sealant obtained by stirring and casting the two-component sealant composition prepared in each of the Examples and Comparative Examples in an atmosphere at 23° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. In this specification, (meth)acrylic means acrylic or methacrylic. In addition, in this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit. In this specification, unless otherwise specified, each component may be used alone or in combination of two or more substances corresponding to that component. When a component contains two or more substances, the content of the component means the total content of the two or more substances. In this specification, unless otherwise specified, the production method of each component is not particularly limited. For example, a conventionally known method may be used. In addition, a commercially available product may be used as each component. In this specification, the polymer (A) having a hydrolyzable silyl group may be simply referred to as "polymer (A)" or "component (A)". The hollow resin body (B) may be simply referred to as "component (B)". The same applies to calcium carbonate (C) and silicon dioxide (D).
[0011] [Stirring device] The present invention will be described in detail below. The stirring device 1 used in the stirring method of the present invention may be a stirring device having a conventional configuration except that the bottom paddle and side paddle satisfy certain conditions, and may have, for example, the configuration shown in Figs. As shown in FIG. 1, the mixing device 1 includes a driving means (not shown) installed in a machine base 2, a rotating table 4 fixed to the upper end of a vertical rotating shaft 3 of the driving means, a mixing container 5 containing an object to be mixed 8 (two-component sealant composition), a paddle 6 that can be inserted into the mixing container 5, and a paddle support means 7 that fixes and supports the paddle 6 so that it can be detached from the machine base 2.
[0012] When mixing materials 8 using this mixing device 1, the materials 8 are placed in the mixing container 5, which is placed on the turntable 4 so that it does not rotate relative to the mixing container 5. The paddle 6 is inserted approximately in the center of the mixing container 5, and the paddle 6 is fixedly supported on the machine base 2 by the paddle support means 7. The turntable 4 is then rotated by the drive means to rotate the materials 8 together with the mixing container 5, while the materials 8 in the mixing container 5 are mixed by the paddle 6.
[0013] The paddle 6 comprises a shaft portion 10 which is inserted vertically into approximately the center of the mixing container 5, an arm portion 11 which extends from the shaft portion 10 toward the inner surface of the mixing container 5, and a stirring portion 12 which extends upward from the outer end of the arm portion 11. The paddle 6 is configured to stir and mix the material to be mixed 8 using a pair of approximately L-shaped left and right paddle main bodies 13 consisting of the arm portions 11 and the stirring portions 12.
[0014] The pair of left and right paddle bodies 13 are set so that lengths L1, L2 of the arm portion 11 from the shaft portion 10 to the stirring portion 12 are different between the left and right paddle bodies 13. However, in addition to lengths L1, L2 of the arm portion 11, the vertical length H of the stirring portion 12 and the vertical length D of the arm portion 11 can also be set to different values between the left and right paddle bodies 13. From the viewpoint of mixability, the length of the shorter arm portion 11 is preferably 75% to 95% of the length of the longer arm portion 11, and more preferably 80% to 90%.
[0015] In the stirring method of the present invention, the average base liquid level LL (mm) when the base is supplied to the mixing vessel 8, the height H (mm) of the pair of side paddles, the average radius X (mm) of the bottom paddle, the initial viscosity A (Pa s) of the base at the temperature during stirring, the initial viscosity B (Pa s) of the base at 5° C., and the cube root C of the value obtained by dividing B by A, Y=(LL-H)×C, are calculated based on the following formula 1: Equation 1 0.2X≦Y≦0.4X Meet the following.
[0016] The average base liquid level height LL (mm) is the average value of the values measured at four points in the vertical direction from the bottom of the mixing container 5 to the liquid level when the entire amount of the base to be mixed is placed in the mixing container 5. The four points are four points that divide the outer circumference of the liquid level of the mixing container 5 at equal intervals, and are determined by selecting the lowest point on the outer circumference by visual inspection and then selecting three points each 90 degrees away from that point.
[0017] The height H (mm) of the pair of side paddles represents the vertical distance from the lowest point to the highest point of the pair of side paddles in the vertical direction. The average radius X of the bottom paddle is calculated by the formula X = (E - 2W) / 2. As shown in Figure 2, E represents the total horizontal length (mm) of the bottom paddle.
[0018] In the above formula 1, B / A is the value obtained by dividing the initial viscosity B (Pa s) of the base at 5° C. by the initial viscosity A (Pa s) of the base at the temperature during stirring. The method for measuring these viscosities and the preferred numerical ranges will be described later.
[0019] It is more preferable that the above formula 1 satisfies 0.2X≦Y. It is also preferable that the above formula 1 satisfies Y≦0.3X. More preferably, the above formula 1 satisfies 0.2X≦Y≦0.3X. By satisfying these numerical ranges, the effects of the present invention are more significantly exhibited.
[0020] The volume S(L) of the two-component sealant composition present at a height from the lowest position to the highest position where the pair of side paddles pass relative to the total volume R(L) of the two-component sealant composition before stirring is expressed by the following formula 2: Formula 2 13≦Z=100×(RS) / R≦23 It is preferable that the following is satisfied. The above formula 2 more preferably satisfies 13≦Z≦21, and even more preferably satisfies 15≦Z≦19. The above Z is a value that indicates the percentage of the volume of the two-component sealant composition that exists in the range where the pair of side paddles are not present, based on the vertical direction, relative to the total volume of the two-component sealant composition to be stirred. The stirring method of the present invention can more reliably exhibit the effects of the present invention by satisfying formula 2 and the above-mentioned preferable numerical range.
[0021] The paddle support means 7 includes a support column 15 fixed in an upright position on one side of the upper surface of the machine base 2, and a support pipe 16 shaped like an inverted J in side view, which is detachably attached to the support column 15. The free end of the support pipe 16 is disposed vertically above a position approximately in the center of the rotating table 4, and the upper end of the shaft portion 10 of the paddle 6 is fitted into the free end of the support pipe 16 and fixed by welding, screws, or the like, whereby the paddle 6 is fixed and supported on the machine base 2 so that the shaft portion 10 is located approximately in the center of the mixing vessel 5.
[0022] The mixing container 5 can be made of a single member, but it is preferable to use a double container made of a hard outer container 20 and a compactly foldable inner container 21, which can be fitted inside the outer container 20 so as not to rotate relative to the outer container 20. The inner container 21 can be disposed of without being reused.
[0023] The inner container 21 preferably comprises a tubular member 22 made of a flexible film material, a bottom plate 23 closing the lower opening of the tubular member 22, an upper annular frame 24 attached to the upper opening of the tubular member 22, and a body annular frame 25 attached to the middle of the height of the tubular member 22, slightly lower than half the height of the inner container 21, and the bottom plate 23 and both annular frames 24, 25 made of a hard resin material are fused to the tubular member 22 made of a film material by heat sealing, ultrasonic sealing, high-frequency induction sealing, etc.
[0024] When the material 8 to be mixed is stirred and mixed using the mixer 1, first, the mixing container 5 filled with the material 8 to be mixed is placed on the turntable 4, and the paddle 6 is fixed to the machine base 2 using a support member so that the shaft 10 of the paddle 6 is positioned approximately on the center line of the turntable 4. Then, the mixing container 5 is rotated together with the turntable 4, and the material 8 to be mixed is stirred and mixed by the paddle main body 13.
[0025] [Sealant composition] The sealant composition to be used in the stirring method of the present invention is preferably a two-component composition having a base material and a curing agent, one of which contains a resin hollow body. Such a sealant composition may be, for example, one disclosed in the specification of JP-A-2021-127357.
[0026] The base of the sealant composition to be subjected to the stirring method of the present invention contains at least a polymer (AA) constituting the main component of the base, and a resin hollow body (B). The main component means that the content of the polymer (AA) is 50 parts by mass or more relative to 100 parts by mass of all components contained in the base (in another preferred embodiment, the content of the polymer (AA) may be 80 parts by mass or more). The content of the resin hollow body (B) is preferably 0.8 to 10 parts by mass, more preferably 1.0 to 8 parts by mass, even more preferably 1.2 to 6 parts by mass, even more preferably 1.4 to 5 parts by mass, and even more preferably 1.5 to 4 parts by mass relative to 100 parts by mass of the base.
[0027] The polymer constituting the main component of the sealant composition to be subjected to the stirring method of the present invention is preferably a polymer (A) having a hydrolyzable silyl group. The sealant composition to be subjected to the stirring method of the present invention is more preferably a sealant composition containing the polymer (A) having a hydrolyzable silyl group, a hollow resin body (B), calcium carbonate (C), and silicon dioxide (D). The sealant composition further preferably contains 0.1 to 10 parts by mass of the hollow resin body (B), 100 to 300 parts by mass of calcium carbonate (C), and 0.1 to 10 parts by mass of silicon dioxide (D) relative to 100 parts by mass of the polymer (A) having a hydrolyzable silyl group.
[0028] <<Polymer (A)>> The sealant composition to which the stirring method of the present invention is applied contains a polymer (AA) which constitutes the main component of the base. The polymer (AA) is preferably one which contains a polymer (A) having a hydrolyzable silyl group as the main component. In this specification, the polymer (AA) is referred to as a generic term for the polymer (A) having a hydrolyzable silyl group. The polymer (A) can form, for example, a siloxane bond by hydrolysis and condensation of the hydrolyzable silyl group.
[0029] <Hydrolyzable silyl group> The polymer (A) has a hydrolyzable silyl group in the molecule. The hydrolyzable silyl group has a hydrolyzable group bonded to a silicon atom. Examples of the hydrolyzable group include a halogen atom, an alkoxy group, an acyloxy group, a ketoximate group, an amino group, an amide group, an acid amide group, an aminooxy group, a mercapto group, and an alkenyloxy group. Among them, an alkoxy group is preferred from the viewpoint of achieving superior effects of the present invention. The hydrolyzable silyl group having an alkoxy group as the hydrolyzable group may be referred to as an alkoxysilyl group. A part of the hydrolyzable groups may be hydrolyzed to form silanol groups.
[0030] The hydrolyzable silyl group includes, for example, a group represented by the following formula (1). -SiR 1 3-a (OR 2 ) a (1) In formula (1), R 1 、 R 2 each independently represents a hydrocarbon group, and a represents 1 to 3.
[0031] R 1 , R 2 The hydrocarbon group as the alkyl group is not particularly limited, and examples thereof include an aliphatic hydrocarbon group (straight-chain, branched, or cyclic), an aromatic hydrocarbon group, or a combination thereof. R 1 is preferably an aliphatic hydrocarbon group or a phenyl group, more preferably a methyl group, ethyl group, propyl group, butyl group, or a phenyl group, more preferably a methyl group, ethyl group, propyl group, or a butyl group, and even more preferably a methyl group or an ethyl group. R 2 is preferably an aliphatic hydrocarbon group. 2 is preferably a methoxy group, an ethoxy group, a propoxy group or a butoxy group, more preferably a methoxy group or an ethoxy group, and further preferably a methoxy group. In view of obtaining superior effects of the present invention, a is preferably 2 to 3, and more preferably 2.
[0032] (Main Chain) The main chain of the polymer (A) is preferably an organic polymer whose skeleton contains at least carbon. Examples of the main chain of the polymer (A) include polyether polymers (such as polyoxyalkylene), (meth)acrylic acid ester polymers, ether / ester copolymers, polymers of ethylenically unsaturated compounds, and polymers of diene compounds. The hydrolyzable silyl group can be bonded to the end or side chain of the main chain. The hydrolyzable silyl group can be bonded to the main chain directly or via an organic group. The organic group is not particularly limited.
[0033] The polymer (A) is preferably a polyether-based polymer, a (meth)acrylic acid ester-based polymer, an ether / ester copolymer, a polymer of an ethylenically unsaturated compound, or a polymer of a diene-based compound, each having a hydrolyzable silyl group, more preferably a polyether-based polymer having a hydrolyzable silyl group, even more preferably a polyoxypropylene-based polymer having a hydrolyzable silyl group, and particularly preferably a polyoxypropylene-based polymer having an alkoxysilyl group.
[0034] As the polymer (A), a commercially available product may be used. Among the polymers (A), the polyether having a hydrolyzable silyl group is commercially available as a so-called "modified silicone". Examples of such commercially available products include MSP-S203, S303, S810 (trade names, manufactured by Kaneka Corporation), ES-S2410, ES-S2420, ES-S3430, ES-S3630, and ES-S2730C (trade names, manufactured by Asahi Glass Co., Ltd.). Of the polymers (A), commercially available (meth)acrylic acid ester polymers having a hydrolyzable silyl group include, for example, SA100S, SA310S, and XX009S (trade names, manufactured by Kaneka Corporation).
[0035] <<Resin hollow body (B)>> The composition to be subjected to the stirring method of the present invention preferably contains a hollow resin body (B). It is preferable that the resin hollow body (B) has an outer shell made of resin and is hollow inside.
[0036] Examples of materials for the outer shell of the resin hollow body (B) include thermoplastic resins such as phenolic resins; urea resins; polystyrene-based resins; polyvinylidene chloride; and acrylonitrile-based copolymers (e.g., copolymers of acrylonitrile and methacrylonitrile, copolymers of acrylonitrile and vinyl monomers such as butadiene and styrene that are copolymerizable with acrylonitrile, etc.).
[0037] From the viewpoints of obtaining superior effects of the present invention and excellent weather resistance, the resin hollow body (B) preferably contains a hollow body of an acrylonitrile copolymer.
[0038] The surface of the hollow resin body (B) may be coated with a filler, such as calcium carbonate, talc, or titanium oxide. From the viewpoint of achieving superior effects of the present invention and superior weather resistance, the above-mentioned resin hollow body (B) is preferably coated with the above-mentioned filler, more preferably coated with calcium carbonate, and further preferably comprises a hollow body of an acrylonitrile-based copolymer coated with calcium carbonate. When the hollow resin body (B) is a hollow resin body coated with calcium carbonate, the calcium carbonate coating the hollow resin body is not included in the calcium carbonate (C) described below. Moreover, the above filler capable of covering the resin hollow body (B) does not contain silicon dioxide (D) which will be described later.
[0039] (Average particle size of hollow resin body (B)) The average particle size of the hollow resin bodies (B) is preferably from 80 to 150 μm, and more preferably from 100 to 140 μm. In the present invention, the average particle size of the hollow resin bodies (B) can be measured by a laser diffraction method.
[0040] In the present invention, when the average particle diameter of the hollow resin body (B) is expressed as a numerical range (e.g., A to B μm), the median value of the numerical range of the average particle diameter of the hollow resin body (B) (i.e., (A+B) / 2) can be treated as the average particle diameter of the hollow resin body (B). When the average particle diameter of the hollow resin body (B) is expressed as a numerical range, the average particle diameter (the above median value) of the hollow resin body (B) is preferably 80 to 150 μm, more preferably 100 to 140 μm, and even more preferably 115 to 130 μm, from the viewpoint of achieving superior effects of the present invention.
[0041] (True specific gravity of resin hollow body (B)) From the viewpoint of obtaining superior effects of the present invention, the true specific gravity of the resin hollow body (B) is 0.05 to 0.35 g / cm 3 is preferable, and 0.07 to 0.12 g / cm 3 is more preferred. The true specific gravity of the hollow resin body (B) refers to the specific gravity determined only from the outer shell of the hollow resin body obtained by finely pulverizing the hollow resin body. The true specific gravity of the hollow resin body (B) can be measured, for example, by a gas displacement pycnometer method (constant volume expansion method) using a dry automatic density meter Accupyc 1330 (product name) manufactured by Shimadzu Corporation.
[0042] In addition, the true specific gravity of the resin hollow body (B) is (for example, C to D g / cm 3 When the true specific gravity is expressed as a numerical range, such as (C+D) / 2, the median value of the numerical range of the true specific gravity of the hollow resin body (B) (i.e., (C+D) / 2) can be treated as the true specific gravity of the hollow resin body (B). When the true specific gravity of the hollow resin body (B) is expressed as a numerical range, the true specific gravity (the above median value) of the hollow resin body (B) is preferably 0.05 to 0.35 g / cm from the viewpoint of obtaining superior effects of the present invention. 3 is preferable, and 0.07 to 0.12 g / cm 3 More preferably, 0.10 to 0.12 g / cm 3 is more preferred.
[0043] <Content of resin hollow body (B)> The content of the resin hollow bodies (B) is 0.1 to 10 parts by mass based on 100 parts by mass of the polymer (A). By ensuring that the content of component (B) is within the above range, the present invention is excellent in design, workability and durability. The content of the component (B) is preferably from 5 to 10 parts by mass, and more preferably from 8 to 10 parts by mass, based on 100 parts by mass of the polymer (A). When the resin hollow body (B) is coated with a filler, the content of the component (B) refers to the amount including the filler.
[0044] <<Calcium carbonate (C)>> From the viewpoint of workability, the composition that is the target of the stirring method of the present invention preferably contains calcium carbonate (C) (component (C)).
[0045] The component (C) is not particularly limited, and examples thereof include untreated calcium carbonate (c-1) and surface-treated calcium carbonate (c-2). The untreated calcium carbonate refers to calcium carbonate that has not been surface-treated. The surface treatment agent used for surface treatment of calcium carbonate is not particularly limited. The surface treatment agent is preferably at least one selected from the group consisting of fatty acids, resin acids, and fatty acid esters, and more preferably contains a fatty acid. The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as caprylic acid, lauric acid, myristic acid, palmitic acid, and stearic acid, and unsaturated fatty acids such as oleic acid, elaidic acid, linoleic acid, and ricinoleic acid.
[0046] (Average particle size of calcium carbonate (C)) From the viewpoints of achieving superior effects of the present invention and excellent mixability of the composition, the average particle size of calcium carbonate (C) is preferably 0.01 to 5.00 μm, more preferably 0.01 to 1.00 μm, and even more preferably 0.01 to 0.1 μm. The average particle size of calcium carbonate (C) refers to the average value of the primary particle size observed with an electron microscope.
[0047] When the component (C) contains untreated calcium carbonate (c-1), the average particle size of the untreated calcium carbonate (c-1) is preferably 0.01 to 5.00 μm, more preferably 0.05 to 3.0 μm, and even more preferably 0.5 to 3.0 μm, from the viewpoints of achieving superior effects of the present invention and superior mixability of the composition.
[0048] When the component (C) contains a surface-treated calcium carbonate (c-2), the average particle size of the surface-treated calcium carbonate (c-2) is preferably 0.01 to 5.00 μm, more preferably 0.01 to 1.00 μm, and even more preferably 0.01 to 0.1 μm, from the viewpoint of excellent mixability of the composition.
[0049] <Calcium carbonate (C) content> The content of calcium carbonate (C) is preferably 100 to 300 parts by mass based on 100 parts by mass of the polymer (A). The content of the component (C) is preferably from 100 to 200 parts by mass, more preferably from 100 to 180 parts by mass, and even more preferably from 120 to 150 parts by mass, based on 100 parts by mass of the polymer (A).
[0050] The calcium carbonate (C) preferably contains untreated calcium carbonate (c-1) and / or surface-treated calcium carbonate (c-2), more preferably contains surface-treated calcium carbonate (c-2), and further preferably contains untreated calcium carbonate (c-1) and surface-treated calcium carbonate (c-2).
[0051] When the calcium carbonate (C) contains surface-treated calcium carbonate (c-2), from the viewpoint of achieving superior effects of the present invention, the calcium carbonate (C) preferably contains surface-treated calcium carbonate (c-2-1) having an average particle diameter of 0.05 to 1.0 μm and / or surface-treated calcium carbonate (c-2-2) having an average particle diameter of 0.01 μm or more and less than 0.05 μm, and more preferably contains the calcium carbonate (c-2-1) and calcium carbonate (c-2-2). The average particle size of the calcium carbonate (c-2-1) is preferably 0.07 to 1.0 μm. The average particle size of the calcium carbonate (c-2-2) is preferably 0.01 to 0.04 μm.
[0052] When the calcium carbonate (C) contains the calcium carbonate (c-2-1) and the calcium carbonate (c-2-2), the mass ratio of the calcium carbonate (c-2-1) to the calcium carbonate (c-2-2) (calcium carbonate (c-2-1) / calcium carbonate (c-2-2)) is preferably 1.0 to 4.0, more preferably 1.5 to 3.0.
[0053] In the case where the calcium carbonate (C) contains untreated calcium carbonate (c-1) and surface-treated calcium carbonate (c-2), the content of the surface-treated calcium carbonate (c-2) is preferably 100 parts by mass or more, more preferably 100 to 200 parts by mass, and even more preferably 100 to 150 parts by mass, based on 100 parts by mass of the polymer (A).
[0054] In the case where the calcium carbonate (C) contains untreated calcium carbonate (c-1) and surface-treated calcium carbonate (c-2), the content of the untreated calcium carbonate (c-1) is preferably 100 parts by mass or more, more preferably 100 to 200 parts by mass, and still more preferably 100 to 150 parts by mass, relative to 100 parts by mass of the polymer (A).
[0055] When the calcium carbonate (C) contains untreated calcium carbonate (c-1) and surface-treated calcium carbonate (c-2), the mass ratio (c-1 / c-2) of the untreated calcium carbonate (c-1) to the surface-treated calcium carbonate (c-2) is preferably 150 / 100 to 100 / 150.
[0056] (Mass ratio of calcium carbonate (C) to hollow resin body (B)) The mass ratio of the content of the calcium carbonate (C) to the content of the hollow resin body (B) (calcium carbonate (C) / hollow resin body (B)) is preferably 10-110, more preferably 15-80, further preferably 15-50, and particularly preferably 15-18.
[0057] <<Silicon dioxide (D)>> The composition that is the target of the stirring method of the present invention preferably contains silicon dioxide (D) (component (D)).
[0058] Examples of component (D) include hydrophilic silica and hydrophobic silica, and component (D) is preferably hydrophilic silica.
[0059] (Average particle size of silicon dioxide (D)) The average particle size of the silicon dioxide (D) is preferably 10 to 20 μm. The average particle size of silicon dioxide (D) refers to the 50% volume cumulative diameter (D50) measured using a laser diffraction particle size distribution analyzer. The particle size used to calculate the average value refers to the average value obtained by dividing the sum of the major axis and minor axis by 2 when the cross section of component (D) is elliptical, and refers to the diameter when the cross section is circular.
[0060] The silicon dioxide (D) may be one obtained by a wet process.
[0061] <Silicon dioxide (D) content> The content of silicon dioxide (D) is preferably 0.1 to 10 parts by mass based on 100 parts by mass of polymer (A). The content of component (D) is preferably 1 to 9 parts by mass, more preferably 5 to 8 parts by mass, based on 100 parts by mass of polymer (A).
[0062] (Mass ratio of silicon dioxide (D) to hollow resin body (B)) From the viewpoint of obtaining superior effects of the present invention, the mass ratio of the content of the silicon dioxide (D) to the content of the hollow resin body (B) (silicon dioxide (D) / hollow resin body (B)) is preferably 0.1 to 7.0, more preferably 0.5 to 2.0, and even more preferably 0.5 to 1.0.
[0063] The above base preferably has an initial viscosity of 1200 to 3200 Pa s, and more preferably 1500 to 2900 Pa s, at 5°C when measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., rotor No. 7) at a rotation speed of 1 rpm. Under the same conditions, the above base preferably has an initial viscosity of 700 to 2700 Pa s, and more preferably 1000 to 2400 Pa s, at 23°C.
[0064] (hardening agent) The curing agent constituting the two-component sealant composition which is the subject of the stirring method of the present invention contains a curing catalyst. The curing catalyst is not particularly limited as long as it is a compound capable of curing the polymer (AA), and examples thereof include tin-based catalysts, titanium-based catalysts, zirconium-based catalysts, aluminum-based catalysts, and amine-based catalysts. Among these, tin-based catalysts are preferred from the viewpoint of excellent curability.
[0065] Examples of tin-based catalysts include tin carboxylates such as tin butanoate, tin octoate, tin caprylate, and tin oleate (excluding alkyltin carboxylates described below); Alkyltin carboxylates such as dibutyltin diacetate, dibutyltin dioctate, dibutyltin dilaurate, dibutyltin dioleate, dioctyltin dilaurate; Alkyl tin oxides such as dibutyltin oxide; Included are alkyltin alkoxides such as dibutyltin dimethoxide.
[0066] The tin-based catalyst is preferably a tin carboxylate, more preferably tin octoate. An example of the stannous octoate is stannous 2-ethylhexylate.
[0067] The content of the curing catalyst is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the polymer (A) from the viewpoints of achieving better effects of the present invention and excellent curability.
[0068] (Additives) The composition to be subjected to the stirring method of the present invention may further contain additives, if necessary, within the range not impairing the purpose or effect. Examples of the additives include plasticizers, organic solvents, antioxidants, thixotropic agents other than calcium carbonate (C) and silicon dioxide (D), and fillers other than calcium carbonate (C) and silicon dioxide (D). The above-mentioned additives are not particularly limited and can be appropriately selected.
[0069] Examples of the plasticizer include aromatic carboxylate plasticizers such as diisononyl phthalate; Aliphatic carboxylic acid ester plasticizers; Epoxy plasticizers such as epoxy hexahydrophthalic acid dialkyl esters, such as epoxy hexahydrophthalic acid dialkyl esters (di-2-ethylhexyl epoxy hexahydrophthalate); Included are polyoxyalkylene polyols such as polyoxypropylene diol. From the viewpoint of obtaining superior effects of the present invention, it is preferable to use the above plasticizers in combination with an aromatic carboxylic acid ester plasticizer, an epoxy plasticizer, and a polyoxyalkylene polyol. The content of the plasticizer is preferably from 10 to 200 parts by mass, and more preferably from 50 to 100 parts by mass, relative to 100 parts by mass of the polymer (A).
[0070] The composition to be subjected to the stirring method of the present invention is a two-component type having a base and a curing agent. The base constituting the composition that is the target of the stirring method of the present invention may contain a polymer (A), hollow resin bodies (B), calcium carbonate (C) and silicon dioxide (D). On the other hand, the curing agent means a curing agent in the broad sense, and the curing agent can contain the curing catalyst as a curing agent in the narrow sense (a component capable of curing the polymer (A)). The above additives may be contained in the base and / or the hardener.
[0071] The composition to which the stirring method of the present invention is applied is one in which the base and the hardener are stored in separate containers, and the base and the hardener are mixed together when used.
[0072] The composition which is the subject of the stirring method of the present invention can be used as a composition for a sealant.
[0073] Examples of substrates to which the composition that is the subject of the stirring method of the present invention can be applied include concrete, wood, metal, glass, plastic, ceramic, and stone. The method for applying the composition to the substrate, which is the subject of the stirring method of the present invention, is not particularly limited, and may be, for example, a conventionally known method.
[0074] (dye) The sealant composition to be used in the stirring method of the present invention may contain a pigment in order to impart a color tone to the resulting sealant. Pigments are classified into inorganic pigments and organic pigments. Examples of inorganic pigments include metal oxides such as titanium dioxide, zinc oxide, ultramarine, and red iron oxide, and sulfides, hydrochlorides, and sulfates of lithopone, lead, cadmium, iron, cobalt, and aluminum. Examples of organic pigments include azo pigments and copper phthalocyanine pigments.
[0075] (True specific gravity of the sealant composition to be subjected to the stirring method of the present invention) The true specific gravity of the sealant composition (all components including the base, curing agent, and color master) that is the subject of the stirring method of the present invention is 1.24 to 1.04 g / cm 3 is preferably 1.19 to 1.09 / cm 3 is more preferred. EXAMPLES
[0076] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0077] <<Production of the composition>> A composition containing the composition (parts by mass) shown in Table 1 below was stirred with a stirring device to prepare a base for a two-component sealant composition. A hardener containing a tin catalyst, a plasticizer, a filler such as calcium carbonate, etc. was prepared and used as the hardener for the two-component sealant composition. A color master containing a pigment, a plasticizer, etc. was prepared and used as the color master for the two-component sealant composition. The obtained base, hardener, and color master were thoroughly mixed using a stirring device (a rotary mixer for sealant containers manufactured by Nippon Sosei Kogyo Co., Ltd. (product name: Karumaze)) to produce a composition.
[0078] [Table 1]
[0079] Details of each component shown in Table 1 are as follows. <Component (A)> Polymer with hydrolyzable silyl groups (A): A polymer having dimethoxysilyl groups as hydrolyzable silyl groups at both ends and a polyoxypropylene main chain. Product name: "MSP-S810", manufactured by Kaneka Corporation.
[0080] <Ingredient (B)> Resin hollow body (B): A hollow body of acrylonitrile copolymer coated with calcium carbonate. Product name: MFL-110CAL, manufactured by Matsumoto Yushi Seiyaku Co., Ltd. True specific gravity: 0.07-0.09g / cm 3, average particle diameter: 90 to 120 μm. The median true specific gravity of the resin hollow body (B) 1 is 0.08 g / cm3, and the median average particle diameter is 105 μm.
[0081] <Component (C)> Calcium carbonate (C) 1: Colloidal calcium carbonate surface-treated with a fatty acid. Product name: Hakuenka CCR, manufactured by Shiraishi Kogyo Co., Ltd. Average particle size: about 0.08 μm. The calcium carbonate (C) 1 used in this example corresponds to the calcium carbonate (c-2-1) in this specification that has been surface-treated and has an average particle size of 0.05 to 1.0 μm.
[0082] Calcium carbonate (C) 2: Colloidal calcium carbonate surface-treated with a fatty acid. Product name: Viscoexcel-30, manufactured by Shiraishi Kogyo Co., Ltd. Average particle size: 0.03 μm. The calcium carbonate (C) 2 used in this example corresponds to the calcium carbonate (c-2-2) in this specification that has been surface-treated and has an average particle size of 0.01 μm or more and less than 0.05 μm.
[0083] <Ingredient (D)> Silicon dioxide (D): Hydrophilic silica produced by the wet process. Product name: Carplex #80, manufactured by DSL. Japan. Average particle size: approx. 15 μm
[0084] Plasticizer 1: Diisononyl phthalate. Product name "DINP", manufactured by J-Plus Co., Ltd. Plasticizer 2: Epoxy plasticizer. Di(2-ethylhexyl) epoxy hexahydrophthalate. Product name: Sanso Cizer E-PS, manufactured by New Japan Chemical Co., Ltd. Plasticizer 3: Polyoxypropylene diol (PPG). Product name: PREMINOL S4012, manufactured by AGC Corporation
[0085] <Shape of paddle used for stirring> The paddle shown in Fig. 3 was used in the stirring tests in Examples 1 to 8 and Comparative Examples 1 to 4. As shown in Fig. 3, the lengths L1 and L2 of the arm portion 11 (the lengths from the outer periphery of the rotating shaft 10 to the inner periphery of the stirring portion 12) were 69.5 mm and 59.5 mm, respectively. The height of the stirring portion 12 was 88.5 mm. The total horizontal length of the arm portion 11 was 203 mm.
[0086] <Blend amount> The weights and volumes of the base, curing agent, and pigment constituting the two-component sealant compositions used in the stirring tests in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Tables 2 and 3. The initial viscosity of the composition was measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., No. 7 rotor) at a rotation speed of 1 rpm at 5°C or 23°C (unit: Pa s).
[0087] [Table 2]
[0088] [Table 3]
[0089] <<Evaluation>> The two-component sealant composition stirred in each of Examples 1 to 8 and Comparative Examples 1 to 4 was poured so as to fill (completely fill) the joints (width: 40 mm, depth: 20 mm, length: 1,000 mm). Pouring was carried out immediately after stirring. After pouring, the surface of the poured composition was made uniform with a metal spatula. Then, each composition was left to cure for 7 days under conditions of 5°C or 23°C and 50% RH (relative humidity) to prepare a sealant. Photographs of the prepared sealants are shown in Figures 4 and 5.
[0090] (mixability) The color of the surface of the sealant mixed and cast in each of Examples 1 to 8 and Comparative Examples 1 to 4 was visually confirmed. Those with a uniform color were rated as "◎". Those with a practically uniform color, although not completely, were rated as "○". Those with some unevenness in color were rated as "△". The results are shown in Tables 2 and 3.
[0091] (Surface unevenness) In Examples 1 to 8 and Comparative Examples 1 to 4, the surface irregularities (pockets) of the mixed and cast sealants were visually confirmed. The number of visually confirmed surface irregularities was counted. The results are shown in Tables 2 and 3.
[0092] (Other measurements) The viscosity and TI value after mixing of the sealants prepared in Examples 1 to 8 and Comparative Examples 1 to 4, and the adhesiveness after curing for 7 days at room temperature, at high temperature, and in the presence of water were confirmed. In all of Examples 1 to 8 and Comparative Examples 1 to 4, no problems were found in these physical properties that would cause problems in their practical use as sealants.
[0093] The sealants cast in Examples 1 to 8 had a lower degree of surface unevenness than the sealants cast in Comparative Examples 1 to 4. It was confirmed that the sealants cast in Examples 1, 2, 5, and 6 were mixed more uniformly than the sealants cast in Examples 3, 4, 7, and 8. Among these, Examples 1 and 5 were particularly excellent in terms of a good balance between mixability and surface unevenness.
Claims
1. A method for stirring a two-component sealant composition comprising a base containing a resin hollow body and a curing agent, the method comprising the steps of: The two-component sealant composition is mixed using a stirring device having a cylindrical mixing container with a bottom into which the two-component sealant composition is supplied, a rotating shaft rotatably provided in the center of the mixing container by a driving device, a bottom paddle provided at the lower end of the rotating shaft, and a pair of side paddles extending from both ends of the bottom paddle along the inner wall of the mixing container to the upper end, The average base liquid level LL (mm) when the base is supplied to the mixing vessel, the height H (mm) of the pair of side paddles, the average radius X (mm) of the bottom paddle, the initial viscosity A (Pa·S) of the base at the temperature during mixing, the initial viscosity B (Pa·S) of the base at 5° C., and the cube root C of the value obtained by dividing B by A, Y=(LL−H)×C, are expressed by the following formula 1: Formula 1 0.2X≦Y≦0.4X A stirring method characterized in that the above-mentioned is satisfied.
2. 2. The stirring method according to claim 1, wherein the resin hollow bodies are contained in an amount of 0.8 to 10 parts by mass relative to 100 parts by mass of the base.
3. The volume S(L) of the two-component sealant composition present at a height from the lowest position to the highest position where the pair of side paddles pass relative to the total volume R(L) of the two-component sealant composition before stirring is expressed by the following formula 2: Formula 2 13≦Z=100×(RS) / R≦23 The stirring method according to claim 2 , wherein the above formula (1) is satisfied.
4. A method for manufacturing a sealant, comprising the steps of: stirring a two-component sealant composition comprising a base containing hollow resin bodies and a curing agent by the stirring method described in claim 1; and applying the stirred two-component sealant composition to an object.
Citation Information
Patent Citations
Paddle of mixer
JP1995039740A
Paddle, and mixer and mixing method using the same
JP2006204980A
A sealing material for buildings
JP2014015530A
Sealant composition
JP2021127357A
mixer paddle
JP3044591U